Delay in skeletal maturity in Malawian children. - Lewis, C; Lavy, C; Harrison, W (2002)
The atlas of Greulich and Pyle for skeletal maturity and epiphyseal closure is widely used in many countries to assess skeletal age and to plan orthopaedic surgery. The data used to compile the atlas were collected from institutionalised American children in the 1950s. In order to determine whether the atlas was relevant to subSaharan Africa, we compared skeletal age, according to the atlas, with chronological age in 139 skeletally immature Malawian children and young adults with an age range from 1 year 11 months to 28 years 5 months. The height and weight of each patient were also measured in order to calculate the body mass index. The skeletal age of 119 patients (85.6%) was lower than the chronological age. The mean difference was 20.0+/-24.1 months (t-test, p = 0.0049), and the greatest difference 100 months. The atlas is thus inaccurate for this group of children. The body mass index in 131 patients was below the normal range of 20 to 25 kg/m2. The reasons for the low skeletal age in this group of children are discussed. Poor nutrition and chronic diseases such as malaria and diarrhoea which are endemic in Malawi are likely to be contributing factors. We did not find any correlation between the reduction in body mass index in our patients and the degree of retardation of skeletal age.